Seasonal Variation of the Flavonoids Pinocembrin and 3-O-Methylgalangin, in the Surface Component Mixture (Resinous Exudates and Waxy Coating) of Heliotropium Stenophyllum - Urzua-Moll, A; Torres-Gaona, M; Modak-Canobra, B (Sociedad Chilena de Quimica, 2011)
In this report we study the seasonal variation of the flavonoids pinocembrin and 3-O-methylgalangin in the surface component mixture (resinous exudate and waxy coating) of Heliotropium stenophyllum. The quantitative analysis of the flavonoids was performed using high-performance liquid chromatography of samples collected monthly over a whole year. The results showed an increase in the spring and summer yield of surface components and a decrease during the winter. Although the sum of pinocembrin and 3-O-methylgalangin did not follow a pattern related with hydric stress, UV radiation or high temperature during the year, a relationship between pinocembrin and 3-O-methylgalangin was found. On average during the months of September to August, excluding March, the amount of pinocembrin decreased wile the amount of 3-O-methylgalangin increased. The results suggest that the above compounds may play different ecophysiological functions during plant development and are consistent with the biosynthetic relationship between the two compounds.